Optimalisasi Penggunaan Kitosan Limbah Kulit Udang Vannamei sebagai Koagulan dalam Perbaikan Kualitas Air Danau - Shabriyani Hatma; Setyawati Yani; A. Suryanto (Journal of Bioprocess, Chemical and Environmental Engineering Science, 2020)
The lake in UNHAS is thought to have experienced pollution which causes the water quality to be poor so that it cannot be utilized at all. For that we need a way to improve water quality. In this study, a natural coagulant was used, namely chitosan from Vannamei shrimp shell waste from KIMA which from the past until now has not been optimally managed, so that it is an aspect that also needs attention. The method used was a jar test, through rapid mixing and slow mixing processes with variants of increasing the concentration of chitosan 0.5, 1, 1.5, 2, 2.5 (%) at stirring speed of 100, 300, 500, and 70 rpm. The results of the study, namely the effect of shrimp shell chitosan on lake water quality for TDS testing showed that, the more addition of chitosan which was parallel with the stirring speed, the solid content decreased so that the shrimp shell chitosan as a coagulant was indeed quite good to be used as an alternative to improve lake water quality in reducing solids content. Optimal at a stirring speed of 500 rpm with the addition of the concentration of chitosan as much as 10 ml / 2.5% to the volume of the lake water sample.